Implementation of E-Kinerja in Increasing Work Productivity - Eritrina Eritrina; Andi Cudai Nur; Andi Aslinda; Herman H (Jurnal Ad'ministrare, 2023)
This research aims to determine the implementation of E-Kinerja in increasing work productivity at the Borong Village office, Manggala District, Makassar City. This type of research is qualitative using a descriptive approach. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique used consists of data collection, data display, data condensation, and drawing conclusions. The results of the research show that the implementation of E-Kinerja in increasing employee work productivity at the Brong Subdistrict Office, Manggala District, Makassar City is good and has experienced improvement using indicators from the theory put forward by George C Edward III, namely Communication, Resources, Disposition and Bureaucratic Structure, although the disposition indicators are still not going well. This can be seen from the communication process carried out by users at the Borong Subdistrict office, both fellow employees at the Subdistrict office and the BKPSDMD during the socialization held at a hotel by the BKPSDMD to all civil servant in Borong Subdistrict. The existing resources at the Borong Subdistrict office have begun to increase from the previous year seen from the availability of employees at the Borong Subdistrict office, they are ready to run the E-Kinerja program because E-Kinerja is an application for assessing performance which is the basis for calculating the provision of TPP  to all ASN in Borong Village. The disposition to carry out bureaucratic arrangements at the Borong Subdistrict office has not been implemented well because there are still several employees who have been absent and disappeared or have not remained in the office during working hours. The bureaucratic structure at the Borong Subdistrict office has  been running well, as seen from the responsibilities in carrying out their duties, employees have carried them out in accordance with applicable SOPs, as seen from the division of responsibilities between each superior who validates the work of their subordinates.